2020
DOI: 10.4085/1062-6050-0093.20
|View full text |Cite
|
Sign up to set email alerts
|

Compression Wrapping for Acute Closed Extremity Joint Injuries: A Systematic Review

Abstract: Objective Current prehospital recommendations for an acute closed extremity joint injury (ACEJI) are to apply compression in some manner. However, the effectiveness of compression is unclear. We performed a systematic review to summarize and synthesize the evidence for the use of a compression bandage for ACEJI in the prehospital setting. Data Sources Cochrane Library, PubMed, and Embase were searched for relevant literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
0
10
0
3
Order By: Relevance
“…The task force requested a SysRev to identify and analyse the evidence about treatment of these injuries. 138 The evidence, consisting of only in-hospital RCTs, found that compression wraps did not reduce pain 139,140 or swelling 139,141,142 or improve range of motion. 139À141, 143,144 One small randomized trial found that a compression wrap did reduce recovery time and shorten time to return to sports.…”
Section: Compression Wrap For Closed Extremity Joint Injurymentioning
confidence: 99%
“…The task force requested a SysRev to identify and analyse the evidence about treatment of these injuries. 138 The evidence, consisting of only in-hospital RCTs, found that compression wraps did not reduce pain 139,140 or swelling 139,141,142 or improve range of motion. 139À141, 143,144 One small randomized trial found that a compression wrap did reduce recovery time and shorten time to return to sports.…”
Section: Compression Wrap For Closed Extremity Joint Injurymentioning
confidence: 99%
“…The task force requested a SysRev to identify and analyse the evidence about treatment of these injuries. 138 The evidence, consisting of only in-hospital RCTs, found that compression wraps did not reduce pain 139 , 140 or swelling 139 , 141 , 142 or improve range of motion. 139 , 140 , 141 , 143 , 144 One small randomized trial found that a compression wrap did reduce recovery time and shorten time to return to sports.…”
Section: First Aidmentioning
confidence: 99%
“…1 8 Infografik Erste Hilfe [4,5]. Einige der systematischen Überprüfungen wurden direkt veröffentlicht, darunter "Sofortmaßnahmen bei Präsynkope" [7], "Behandlung von Hypoglykämie" [8], "Frühe versus späte Gabe von Acetylsalicylsäure bei Brustschmerzen nichttraumatischer Genese" [9], "Kühltechniken bei Hitzschlag und anstrengungsbedingter Hyperthermie" [10], "Kompressionsverband bei akuten, geschlossenen Gelenksverletzungen" [11], "Zahnverlust" [12] und "Erkennen eines Schlaganfalls durch Ersthelfer" [13].…”
Section: Bei Einer Thermischen Verletzung Entfernenunclassified
“…Für Eine neue systematische Überprüfung für 2020 wurde von der ILCOR Arbeitsgruppe für Erste-Hilfe durchgeführt, in der die am besten verfügbaren Belege für die Verwendung eines Kom-pressionsverbands zur Behandlung von geschlossenen Gelenkverletzungen an den Extremitäten überprüft wurden [4,5]. Insgesamt wurden 1193 Referenzen identifiziert, von denen schließlich sechs randomisierte, kontrollierte Studien [239,[242][243][244][245][246] und zwei nichtrandomisierte, kontrollierte Versuche [247,248] [4,5,11]. Darüber hinaus konnte die Task Force aufgrund fehlender Evidenzen keine Empfehlung für oder gegen die Verwendung eines Kompressionsverbands für andere geschlossene Verletzungen von Gelenken, abgesehen von Knöchelverletzungen, empfehlen.…”
Section: Kompressionsverbände Für Geschlossene Gelenkverletzungen An Extremitätenunclassified
See 1 more Smart Citation